Playing with fire. Understanding how experiencing a fire in an immersive virtual environment affects prevention behavior. - Patty C P Jansen; Chris C P Snijders; Martijn C Willemsen (PLoS ONE, 2020)
A potentially effective way to influence people's fire prevention behavior is letting them experience a fire in an immersive virtual environment (IVE). We analyze the effects of experiencing a fire in an IVE (versus an information sheet) on psychological determinants of behavior-knowledge, vulnerability, severity, self-efficacy, and locus of control-based mainly on arguments from Protection Motivation Theory and the Health Belief Model. Crucial in our setup is that we also relate these determinants to actual prevention behavior. Results show that IVE has the hypothesized effects on vulnerability, severity, and self-efficacy, and an unexpected negative effect on knowledge. Only knowledge and vulnerability showed subsequent indirect effects on actual prevention behavior. There remains a direct positive effect of IVE on prevention behavior that cannot be explained by any of the determinants. Our results contradict the implicit assumption that an induced change in these psychological determinants by IVE, necessarily implies a change in behavior. A recommendation for research on the effects of IVE's is, whenever possible, to study the actual target behavior as well.